Human Rights Enforcement in Indonesia During a Pandemic: A Critical Study of Dignified Education - Franciscus Xaverius Wartoyo; Teguh Prasetyo (Catuspata, 2021)
This article was writting to describe government policies in upholding educational rights, especially during a pandemic with its implementation in the field of education according to the theory of dignified justice. Qualitative descriptive method was used in reviewing the problems described, using content analysis method, namely examining the contents of the document. The theoretical basis is used as a guide to adapt the research approach to reality. For the sake of simplicity, qualitative method sources are used in reference studies from various existing research results. The data analysis method uses deductive analysis techniques that use logic to draw one or more conclusions based on a particular field. The role of the state and citizens in dealing with the covid-19 pandemic, especially in the field of education, needs to be synchronized so that citizens, especially middle and lower education, SMA to SD and Kindergarten, the role of parents is very important in the continuity of the online learning process because the teacher's role has changed completely from the beginning. dominated by schools when learning is online, the role of teachers and schools is reduced. This raises its own problems so that the responsibility for education is a shared responsibility in terms of supervision in using online learning media, because this is a disaster category so that human rights violations do not occur, it is necessary to change the view of education that is handed over to schools now it is a shared responsibility so that create a dignified education. The government's policy to protect people's education is always implemented by making education a priority work program of the government, among other programs. This means that the education budget is in accordance with the 1945 Constitution of the Republic of Indonesia Article 31 paragraph (4),